Предмет: Математика,
автор: gebanlk
Упростить выражажение sin(x-pi)cos(x+2pi)sin(4pi-x)/sin(p/2+x)ctg(2pi-x)ctg(3pi/2+x)
Приложения:
![](https://files.topotvet.com/i/afb/afb64913baa07243fdedc9a733256f6d.jpg)
Ответы
Автор ответа:
0
[sin(x-π)*cos(x+2π)*sin(4π-x)]/[sin(π/2+x)*ctg(2π-x)*ctg(3π/2+x)]=
=[-sinx*cosx*(-sinx)]/[cosx*(-ctgx)*(-tgx)]=sin²x*cosx/(cosx*1)=sin²x
=[-sinx*cosx*(-sinx)]/[cosx*(-ctgx)*(-tgx)]=sin²x*cosx/(cosx*1)=sin²x
Похожие вопросы
Предмет: Физика,
автор: arujan2411
Предмет: История,
автор: infuzoria111tufelki
Предмет: История,
автор: ni346771
Предмет: Литература,
автор: vova2907
Предмет: Литература,
автор: liudasergeenko